1991
DOI: 10.1017/s0043174500088470
|View full text |Cite
|
Sign up to set email alerts
|

Salt Antagonism of Glyphosate

Abstract: Glyphosate is often applied with diammonium sulfate to increase weed control. However, many other salts in the spray carrier have antagonized glyphosate phytotoxicity. Research was conducted with wheat as a bioassay species to further determine the influence of various salts on glyphosate phytotoxicity. Cation antagonism of glyphosate occurred with iron > zinc > calcium ≥ magnesium > sodium > potassium. Ammonium cation with hydroxide or most other anions was not antagonistic. Anions of ammonium com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 11 publications
(2 reference statements)
3
89
0
3
Order By: Relevance
“…Researchers have shown that the activity of glyphosate can be affected by carrier volume (Sanberg et al 1978;Stahlman and Phillips 1979). Most believe this is attributed to water hardness (Hatzios and Penner 1985;Nalewaja and Matysiak 1991). Water is determined to be hard if specific cations, such as Ca ++ and Mg ++ , are 100 ppmw or higher.…”
Section: L/ha --------------------------------------% ---------------mentioning
confidence: 99%
“…Researchers have shown that the activity of glyphosate can be affected by carrier volume (Sanberg et al 1978;Stahlman and Phillips 1979). Most believe this is attributed to water hardness (Hatzios and Penner 1985;Nalewaja and Matysiak 1991). Water is determined to be hard if specific cations, such as Ca ++ and Mg ++ , are 100 ppmw or higher.…”
Section: L/ha --------------------------------------% ---------------mentioning
confidence: 99%
“…Studies on the reasons for tolerance are rare. Calcium is a well‐known antagonistic ion when present in water used for spraying 21. However, calcium and magnesium, which is similarly antagonistic, are also present on the leaf surfaces of many plants 8.…”
Section: Use In Cropping Systemsmentioning
confidence: 99%
“…It is well established that polyvalent cations found in hard waters can antagonise the activity of the herbicide glyphosate [ N ‐(phosphonomethyl)glycine] 1–4. This antagonism is believed to result from the formation of glyphosate salts of low solubility which are less readily taken up into the plant with a consequent decrease in herbicidal activity 5–7.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that AMS alleviates cation antagonism through the precipitation of insoluble calcium sulphate 2, 4. Other work has shown that interactions between ammonium ions and glyphosate are also important 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation